Flow cytometric Analysis of Acute Promyelocytic Leukemia: A Series of Four Cases with Review of Literature - Swati Agarwal; Gunja Dwivedi; Vijay Rajak; Rajani Rajkumari (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2024)
Acute Promyelocytic Leukemia (APL) is an aggressive form of Acute Myeloid Leukemia (AML), a cancer of the bone marrow. APL causes accumulation of promyelocytes in the peripheral blood and bone marrow and is associated with translocation t(15; 17). The diagnosis of APL can be made with the help of a complete blood count, peripheral blood film examination, bone marrow, and flow cytometry. Immunophenotypically, APL is characterized by positivity for CD117 and cMPO, bright positivity for CD33 and CD13, and negative for CD34 and HLA-DR. Here, we present four cases suspected of acute leukemia on peripheral blood film and bone marrow examination and diagnosed as APL in flow cytometric analysis.